Red sky mourning - Carr, Jack (Joint pseudonym) (Carr, Jack (Joint pseudonym). Terminal list (Series), 2024)
When three seemingly disconnected events are about to ignite a power grab unlike anything the world has seen, Navy SEAL sniper James Reece, to save America, must reconnect to a quantum computer called "Alice" who is positioned to act as either the county's greatest savior or its worst enemy.